The Economics of Regional Poverty-Environment Programs: An Application for Lao People's Democratic Republic - Buys, Piet; Chomitz, Kenneth; Dasgupta, Susmita; Deichmann, Uwe; Larsen, Bjorn; Meisner, Craig; Nygard, Jostein; Pandey, Kiran; Pinnoi, Nat; Wheeler, David R. (World Bank, Washington, D.C., 2013)
Program administrators are often faced with the difficult problem of allocating scarce resources among regions in a country when interventions are aimed at addressing multiple objectives. One main concern is the tradeoff between poverty reduction and improvement of environmental quality. To provide a framework for analysis, the authors develop a model of optimal budget allocation that allows for variations in three factors: administrators' valuation of objectives; their willingness to accept tradeoffs among objectives and regional allotments; and regional administrative costs. The results from an application of this model using information for Lao People's Democratic Republic show that simple poverty indicators alone do not provide consistent guidelines for policy. However, when different poverty indicators are embedded in an optimizing model that incorporates preferences and costs, the resulting provincial allocations are very similar. This suggests that adoption of a formal analytical approach to resource allocation can help promote the harmonization of regional policy guidelines.